Luminescence and Radiocarbon Dating of Mortars at Milano-Bicocca Laboratories. Issue 3 (14th June 2020) - Panzeri, Laura; Maspero, Francesco; Galli, Anna; Sibilia, Emanuela; Martini, Marco
ABSTRACT: This work shows the results of optically stimulated luminescence (OSL) and radiocarbon ( 14 C) dating applied to mortars of historical structures in northern Italy. All the results are compared with archaeological evidence and thermoluminescence (TL) dating of bricks. The main issue for OSL mortar dating is that the quartz grains contained in the mortar may be only partially bleached, leading to an overestimation of the sample age. In order to identify the best protocol to apply, both multi-grain (MG) and single grain (SG) methods were used. The minimum age model (MAM) statistical approach was applied to refine their accuracy. However, the identification of the bleached grains is not always successful, indicating that further investigations are needed to develop suitable dating protocol. For the 14 C technique, a crucial aspect is the selection of anthropogenic calcite. In this work the mortars were treated using a Cryosonic method to select anthropogenic calcite from raw material, and the obtained powder was sieved to select the finer fraction. Unfortunately, only in two cases an acceptable amount of sample could be obtained. All the fractions were dated via accelerator mass spectrometry (AMS), and the results compared with independently obtained dates. The results show that the execution of the dating analysis requires previous characterizations to assess the nature of the mortar components and avoid unusable fractions.